The role of South African traditional health practitioners in the treatment of HIV/AIDS; A study of their practices and use of herbal medicines - David R Walwyn; Boitumelo Maitshotlo (AOSIS, 2010)
Background A large proportion of HIV positive South Africans regularly consult Traditional Health Practitioners (THPs) for their healthcare needs, despite some evidence of negative interactions with antiretrovirals (ARVs) and no published peer-reviewed clinical evidence for the efficacy of traditional medicines in the treatment of HIV. In this study, we investigated the dominant practices of THPs towards HIV positive patients and whether these practices have changed following widespread public awareness campaigns covering HIV and its treatment. Method The study used a semi-structured interviewer-administered questionnaire in the home language of the interviewee. A total of 52 THPs from four provinces (Gauteng, Limpopo, Kwazulu Natal and Eastern Cape) were interviewed. 38% of the respondents were based in the rural areas, and 69% classified themselves as inyangas, with the remainder being sangomas. Findings All of the THPs in the survey offered treatment for HIV, although only 20% claimed to be able to cure the disease. 88% prepared their own medication, mostly from plant material, and sold their products as aqueous extracts in labelled bottles. None of these products had been systematically evaluated, and there was mostly no record keeping, either of the patient, or of the medicine itself. Quality control practices such as expiry dates, controlled storage conditions and batch records were totally unknown in our sample. Only 38% of the THPs had received training on HIV/AIDS although 75% believed that they were well informed about the disease. Our own assessment was that only 50% had a working knowledge of HIV; more disturbingly 37% believe that only traditional medicines should be used for the treatment of HIV and a further 50% believe that both traditional medicines and ARVs can be taken simultaneously. Interpretation Despite ongoing public educational campaigns on HIV, some of which have specifically targeted THPs, the care of HIV positive patients continues to be compromised by the traditional sector. Although some progress is evident, THP approaches to HIV treatment fails to conform to minimum standards proposed by the World Health Organisation and other organisations, and represents a considerable challenge to the integration of THPs with the biomedical sector, and with the antiretroviral treatment programme in South Africa.